The harmonization of ethnic traditions and cultures: an Islamic perspective - Shehu, Fatmir Mehdi (2015)

(untitled)
In the contemporary time, two major forces dominate most of people’s life: the material entity and the spiritual entity. The de-harmonization of these two entities, material and spiritual, has given birth to economic, political, ethnic, social and religious crises and conflicts. The ethnic crises are considered by this study as one of the major issues to be discussed. Hence, this paper seeks to study the harmonization of ethnic traditions and cultures from the Islamic perspective. For Muslims, Islam is a comprehensive way of life that invites humans to deal with all the problems of life, individual and social, economic and political, national and international, in line with their commitment to God. Although, Muslims come from different ethnicities, yet they have to judge each other as well as non-Muslims according to Shariah (The Islamic Law). Islam considers people’s differences, like race, colour, language, tradition, culture, religion, etc., as Sunnah of Allah (the Divine Custom of God), which bring people closer to one another. The crises and conflicts created by such differences are solved by Islam’s harmonization of people’s outward and inward activities. The purpose of man’s creation as al-Khalifah (the vicegerent) of the Almighty God, Allah (s.w.t.) in Islam is a very crucial point to be discussed here, as it acknowledges human’s universal equality, universal kinship, spiritual unity, and freedom of choice. This paper will examine the status of Muslim and non-Muslim ethnic groups in the Islamic State showing Islam’s approach to the harmonization of their traditions and cultures. This will be illustrated with activities of certain contemporary Muslim organizations and institutions. A descriptive and analytical methodology will be employed by the researcher, who will try to be fair in collecting and discussing the data related to this topic. The researcher believes that the findings of this study will provide solid solutions for the ethnic crises and conflicts found in most of our contemporary societies.